BY INTRODUCING MODERN INFORMATION TECHNOLOGIES CONTRADICTIONS IN COLLECTION OF TAX ACCOUNT DEBT WAYS OF ELIMINATION - Umarov Zhonibek Serikboevich (Web of Journals Publishing, 2024)
Based on the analysis of the advanced reforms being carried out today in our republic, it can be said that the urgent task is to implement fundamental reforms aimed at achieving timely collection of taxes from taxpayers, including business entities and individuals, as well as taking measures to collect existing tax debts at the expense of modernization of modern software products. Further improvement of modern information and communication infrastructure in the tax service, development of information resources and information systems, provision of interactive services to citizens through further improvement of the existing electronic document management system with the websites of interdistrict courts for economic and civil cases and the Executive Bureau under the General Prosecutor's Office of the Republic of Uzbekistan forms the basis of innovations, implemented in tax authorities.
Keywords: taxpayer, business entity, individual, tax debt, software product, information resources, interdistrict courts for economic and civil cases, Bureau of Compulsory Enforcement under the General Prosecutor's Office of the Republic of Uzbekistan, tax service authority for electronic documents.